Pengaruh Experiential Marketing Terhadap Customer Loyalty Pada Pelanggan Restoran Koki Sunda Di Pekanbaru - Tengku Firli Musfar; Vivi Novia (Jurnal Ekonomi, 2012)
This research is conducted to analyze the influence of experiential marketing to customer loyalty at Koki Sunda restaurant in Pekanbaru. The population of the research is the customer of Koki Sunda restaurant. The amount of sample selected three hundred ninty three costumers by using purposive sampling. The research consists of a dependent variable that is customer loyalty and five independent variables which are dimension of experiential marketing: sense, feel, think, act and relate. Data analysis using quantitatif method with SPSS version seventeen. The result of this research convey that all of the independent variables simultaneously affect the customer loyalty positif and significantly. Partially test proved that all variables affect positif and significant to costumer loyalty where sense variable has affected most significantly. Adjusted R square show at fourty five point four percent. It mean fifty four point six percent has affected by other variable beyond this research. Therefore Koki Sunda restaurant should be pay attetion seriously to increase all independent variables to enhance the customer loyalty such as to give cheff sharing payment system, set the time standar in order taking, serve customer more friendly, hold costumer gathering event at Koki Sunda anniversary and provide membercard that will generate point value for members.